Clinical Insights into Bilateral Cochlear Implantation for a Child with Dominant Deafness-Onychodystrophy Syndrome. - Kao, Wei-Ting; Cheng, Yu-Lin; Ho, Pei-Hsuan; Chu, Chia-Huei; Chen, Pey-Yu; Lin, Hung-Ching (Journal of the American Academy of Audiology, 2025)
Background: Dominant deafness-onychodystrophy (DDOD) syndrome is a rare genetic disorder characterized by sensorineural hearing loss and the absence or hypoplasia of nails, associated with defects in the ATP6V1B2 gene. This gene defect significantly affects hearing function, leading to congenital severe-to-profound hearing loss. Purpose: We present the comprehensive cochlear implant (CI) outcome of a 5-year-old child with DDOD syndrome who received bilateral sequential CIs at the ages of 1 and 4 years. Research Design: Case study. Data Collection and Analysis: Retrospective chart review of aural-communication and language performance. Results: After the follow-up following the first CI, there was improvement in auditory, language, and cognitive abilities. At 41 months after the first CI, the child received the second CI. Although his language ability still lagged behind, his auditory and communication performance continued to improve after bilateral CI surgery. He obtained 95 percent on the Parents' Evaluation of Aural/Oral Performance of Children scale at the last follow-up. Conclusions: Children with DDOD syndrome (ATP6V1B2 c.1516C > T) receiving bilateral CIs can enhance aural and communication skills.